Evolution of Audit in Lithuania and the Problems Related to its Establishment - Lakis, Vaclovas (Ekonomika, 2002)
Audit has been known from quite ancient times because when establishment of the states started to avoid mistakes and to prevent from cheating management of economic activity emerged as a priority issue. A three - link system of audit formed up, including governmental audit, independent audit and internal audit. By the goals pursued and the type of activity governmental audit and independent audit are most similar. Both links of the system of audit referred to above can be regarded as institutions of external audit. Internal and external audit are more different than simular. Internal auditors act on a much broader scale yet, in comparison with independence of external auditors their independence is much less. Shortage of experience as well as specific character of functioning of economic mechanism prevented from adopting such system of audit in the Republic of Lithuania which wa. applicable in other countries. In the process of establishment of independent audit two stages can be singled out. Everything was quite slow in the beginning. Development gained pace on the second stage. Establishment of internal audit started most lately and is in the stage of development. Structural divisions are functioning in the banks as well as in state enterprises and institutions. However, quite a lot of problems and drawbacks are confronted with. Divisions of internal audit cannot be traced often in private companies and in enterprises of different types. Presently establishment of the system of audit in the Republic of Lithuania has entered its final stage.